2009
DOI: 10.1097/brs.0b013e3181a3d440
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of Transverse Partial Sacrectomy on the Sacroiliac Joints

Abstract: In surgical treatment of distal sacral tumor, transverse partial sacrectomy involving S1 could result in rotational instability, and the resection level beyond (1/2)S1 further led to compressive instability. When the sacrectomy was at or above the S1/2 level, local reconstruction should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“… 13 Two patients in our series required lumbopelvic fixation in a delayed fashion. Early biomechanical studies by Gunterberg 38 and others 39 , 40 have shown that lumbopelvic stabilization should be strongly considered after sacral amputations extending above the S1-2 junction. The 2 patients in our series who required lumbopelvic fixation both had high sacral amputations at the S1-2 junction and were left with a thin isthmus.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Two patients in our series required lumbopelvic fixation in a delayed fashion. Early biomechanical studies by Gunterberg 38 and others 39 , 40 have shown that lumbopelvic stabilization should be strongly considered after sacral amputations extending above the S1-2 junction. The 2 patients in our series who required lumbopelvic fixation both had high sacral amputations at the S1-2 junction and were left with a thin isthmus.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of techniques have been suggested in pelvic reconstruction after sacrectomy. 7 8 Although pelvic reconstruction is challenging because of anatomical complexity and excessive weight bearing, optimal methods have not yet been developed because of the rarity of sacral lesions. Because there are no ready-made implants, various grafts have been used despite donor site complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have applied offset compression to induce bending 24,25. A few studies have included pure moments in conjunction with follower loads to analyze the motion of the SI joint 26–28. The use of a follower load is thought to stabilize the spine, although its appropriateness is debated.…”
Section: Discussionmentioning
confidence: 99%